The Effect of the Use of Mobile Learning Applications on Students' Listening Skills - Abdul Hamid; Putriwanti Putriwanti; Windhy Chrysty (PT. Anagata Sembagi Education, 2024)
Listening skills are a key element in language learning, serving as the basis for speaking, reading, and writing skills. This study explores the influence of mobile learning applications on students' listening skills, with a qualitative approach and case study design. The research subjects consisted of high school students and English teachers who used mobile learning applications. Data is collected through in-depth interviews, observations, and documentation of test results. The findings show that the use of mobile learning applications significantly improves students' listening skills, strengthens comprehension, and increases motivation to learn independently. Interactive features in the app, such as varied audio, practice questions, and instant feedback, allow students to learn in a more flexible and personalized way. Despite challenges such as the technology access gap, mobile learning apps offer innovative solutions that support inclusive learning. This study recommends the integration of technology in the language learning curriculum to facilitate the development of more effective listening skills. Thus, mobile learning not only improves learning outcomes but also builds students' interest in language learning, preparing them for the challenges of global communication.